High Rates of Native Hawaiian and Older Japanese Adults Hospitalized with Dementia in Hawai'i. Issue 1 (23rd December 2014) - Sentell, Tetine L.; Valcour, Nicole; Ahn, Hyeong Jun; Miyamura, Jill; Nakamoto, Beau; Chow, Dominic; Masaki, Kamal; Seto, Todd B.; Chen, John J.; Shikuma, Cecilia
<x xml:space="preserve">Abstract</x> Data on dementia in Native Hawaiians and many Asian subgroups in the United States are limited. Inpatients with dementia have higher costs, longer stays, and higher mortality than those without dementia. This study compared rates of inpatients with a dementia diagnosis for disaggregated Asian and Pacific Islanders (Native Hawaiian, Chinese, Japanese, Filipino) with those of whites according to age (18–59, 60–69, 70–79, 80–89, ≤90) for all adults hospitalized in Hawai'i between December 2006 and December 2010; 13, 465 inpatients with a dementia diagnosis were identified using International Classification of Diseases, Ninth Revision, codes. Rates were calculated using population size denominators derived from the U.S. Census. In all age categories, Native Hawaiians had the highest unadjusted rates of inpatients with dementia and were more likely to have a dementia diagnosis at discharge at younger ages than other racial and ethnic groups. In adjusted models (controlling for sex, residence location, and insurer), Native Hawaiian inpatients aged 18 to 59 (aRR = 1.50, 95% CI = 0.84–2.69), 60 to 69 (aRR = 2.53, 95% CI = 1.74–3.68), 70 to 79 (aRR = 2.19, 95% CI = 1.78–2.69), and 80 to 89 (aRR = 2.53, 95% CI = 1.24–1.71) were significantly more likely to have dementia than whites, as were Japanese aged 70 to 79 (aRR = 1.30, 95% CI = 1.01–1.67), 80 to 89 (aRR = 1.29, 95% CI = 1.05–1.57), and 90 and older (aRR = 1.51, 95% CI = 1.24–1.85). Japanese aged 18 to 59 had were significantly less likely to have dementia than whites (aRR = 0.40, 95% CI = 0.17–0.94). These patterns have important public health and clinical care implications for Native Hawaiians and older Japanese populations. Future studies should consider whether preventable medical risk, caregiving, socioeconomic conditions, genetic disposition, or a combination of these factors are responsible for these findings.